2022
DOI: 10.3390/v14050909
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the CTRL2 Insulator in HSV-1 Results in the Decreased Expression of Genes Involved in Axonal Transport and Attenuates Reactivation In Vivo

Abstract: HSV-1 is a human pathogen that establishes a lifelong infection in the host. HSV-1 is transported by retrograde axonal transport to sensory neurons in the peripheral nervous system where latent viral genomes can reactivate. The resulting virus travels via anterograde axonal transport to the periphery and can cause clinical disease. CTCF insulators flank the LAT and IE regions of HSV-1 and during latency and maintain the integrity of transcriptional domains through a myriad of functions, including enhancer-bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, several studies have revealed that CTCF can regulate viral gene expression in other double-stranded DNA viruses. For instance, in Kaposi’s sarcoma herpesvirus (KSHV) [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], herpes simplex virus (HSV) [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ] and human cytomegalovirus (CMV) [ 90 ], CTCF has been shown to bind to the viral genome and regulate viral gene expression by modulating the accessibility of the viral genome to transcription factors. Finally, it has also been suggested that viruses can modulate CTCF activity to promote viral replication.…”
Section: Ebv and Ctcfmentioning
confidence: 99%
“…Furthermore, several studies have revealed that CTCF can regulate viral gene expression in other double-stranded DNA viruses. For instance, in Kaposi’s sarcoma herpesvirus (KSHV) [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], herpes simplex virus (HSV) [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ] and human cytomegalovirus (CMV) [ 90 ], CTCF has been shown to bind to the viral genome and regulate viral gene expression by modulating the accessibility of the viral genome to transcription factors. Finally, it has also been suggested that viruses can modulate CTCF activity to promote viral replication.…”
Section: Ebv and Ctcfmentioning
confidence: 99%
“…Subsequent reactivation triggers anterograde axonal movement of the virus towards the periphery, potentially resulting in clinical disease manifestation. 52 Reactivation of HSV plays a pivotal role in instances of fatal encephalitis within the US. It contributes significantly to recurrent herpetic keratitis, a leading cause of blindness.…”
Section: Hsv Latency and Reactivation In The Nervous Systemmentioning
confidence: 99%
“…It is within these neurons that latent viral genomes persist. Subsequent reactivation triggers anterograde axonal movement of the virus towards the periphery, potentially resulting in clinical disease manifestation 52 . Reactivation of HSV plays a pivotal role in instances of fatal encephalitis within the US.…”
Section: Hsv: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation